Interlocuções entre Psicologia e Direitos Humanos: práticas interventoras - Rodrigues, Rafael de Oliveira [UNESP]; Cruz, Soráia Georgina Ferreira de Paiva [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2014)
This intervention research was developed with adolescents of an establishment of care for children and adolescents considered at personal and social risk, in a city located in the state of São Paulo. The care practices found in the mentioned establishment are aimed at “prevention” of children and adolescents who could become offenders or future criminals, since they are selected from the poorest families in the outskirts of the city where the institution is located. Our psychological practice reported here, however, was conceived and put into practice from the discussion on Human Rights and Citizenship which aims to afirm what is considered deviation from the norm, opening spaces for the difference in relation to otherness and to the policy statement of these bodies in the urban setting within which they are inserted.

A presente pesquisa-intervenção foi desenvolvida junto a adolescentes de um estabelecimento de atendimento à infância e adolescência consideradas de risco pessoal e social, situada numa cidade no interior do Estado de São Paulo. As práticas de atendimento que encontramos no estabelecimento em questão visam à “prevenção” de crianças e adolescentes que poderiam se tornar delinquentes e futuros marginais, pois são selecionados dentre as famílias mais pobres da periferia da cidade em que está localizada a Instituição. Nossa prática psicológica aqui relatada, entretanto, foi pensada e colocada em prática com a discussão sobre Direitos Humanos e Cidadania que visa airmar aquilo que é considerado desvio à norma, abrindo espaços para a diferença na relação com a alteridade e para a airmação política desses corpos no cenário urbano em que estão inseridos.
Dialogues between Psychology and Human Rights: intervening practices
Keywords: Psycology; Disciplining; Human rights; Psicologia; Disciplinarização; Direitos humanos